A Study on the Cultural Connotations and Heritage Development of Nanfeng Nuo Dance Masks - Chen, Yuxuan; Suvimolstien, Chusak; Khochprasert, Jantana (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: As an intangible cultural heritage, mask dance holds a profound influence worldwide. Chinese Nuo Dance, particularly the Nanfeng Nuo Dance from Jiangxi Province, is renowned for its distinctive artistic style and rich cultural heritage. However, with rapid social development, the Nanfeng Nuo Dance and its associated mask culture are facing a crisis in inheritance, necessitating an in-depth study of the cultural significance of Nanfeng Nuo Dance masks. Materials and Methods: This study employs a literature review, field investigation, and interdisciplinary research methods to collect historical data on the Nanfeng Nuo Dance and the belief functions of its masks. It aims to analyze their cultural connotations and the challenges of inheritance while offering guidance for the preservation and development of this tradition. Results: The research reveals the rich symbolic meaning of Nanfeng Nuo Dance masks, their diverse deity worship, local cultural influences, and their value in contemporary society. In response to the practical difficulties of inheritance, the study proposes strategies such as enhancing cultural education and promotion, revitalizing intangible cultural heritage resources, building cultural brands, and integrating rural revitalization with cultural inheritance. Conclusion: Based on the research findings, it is evident that the Nanfeng Nuo masks are not only products of an agricultural society but also hold significant cultural heritage value in modern society. This study advocates for enhancing cultural education, revitalizing intangible cultural heritage, and building cultural brands as key strategies to promote the sustainable development of Nanfeng Nuo mask culture.